THE INFLUENCE OF THE BALINESE PHONOLOGICAL SYSTEM ON EFL SOUND ACQUISITION - I Ketut Wardana; Putu Sri Astuti (Journal on Studies in English Language Teaching (JOSELT), 2022)
More evidence is needed to determine if English language sounds are influenced by Balinese EFL students. Therefore, this study attempted to examine the dominance of tonal systems in English and Balinese using dual-coding theory. This study used a qualitative approach to describe the English language of Balinese-speaking students as a segmental category. This study included 76 English students from Denpasar. The instruments consisted of a 65 English word list, a picture list, and ten sentences. The articulatory phonetic and referential techniques were used to classify each data set. Accordingly, the students activated the English system more independently but managed to translate it phonetically into Balinese. The phonetic translation, on the other hand, can be pure English, mixed Balinese, and English, or simply pure Balinese. This tendency is influenced by students' phonological awareness, learning experience, and daily practice. According to the results of this study, the four levels of English pronunciation by students are transcription, perception, phonological process, and phonetic translation. At the level of perception, the Balinese sound system is activated in English. This study suggests that English learners and teachers in Bali should use explicit learning to reduce pronunciation errors.